A systematic review and meta-analysis of the accuracy of the clock drawing test (CDT) in the identification of delirium in older hospitalised patients. (4th May 2021) - Meagher, David; Williams, Olugbenga Alaba; O'Connell, Henry; Leonard, Maeve; Cullen, Walter; Dunne, Colum P.; Mulligan, Owen; Adamis, Dimitrios
Abstract: Objective: Delirium is a common neurocognitive syndrome among hospitalised older adults. The clock drawing test (CDT) is a relatively simple bedside test of cognitive function. This systematic review and meta-analysis examine the accuracy of the CDT in identifying delirium in hospitalised older adults. Methods: PRISMA guidelines were used to report the identified studies. Pubmed, SCOPUS, and Ovid and EBSCO platforms (including MEDLINE ®, PsycINFO, PsycEXTRA, EMCARE, CINAHL and EMBASE databases) were searched. Studies were assessed for methodological quality using the Downs and Black Tool. Data were extracted regarding the number of delirious/not delirious, number with normal and abnormal CDT, age, and MMSE scores, and information regarding CDT scoring, criteria for diagnosis of delirium and setting of the study. Analysis was carried out with the "Mada" and "Metatron" packages of R software. Results: Fifteen studies were examined. The number of participants was 2199, of whom 597 (27.15%) were diagnosed with delirium. The overall sensitivity of CDT in the absence of any formal cognitive test was 0.76 (0.58–0.87) with specificity of 0.70 (0.51–0.83). When the MMSE was taken into account, the specificity and sensitivity reduced to 0.51. Diagnostic criteria for delirium, scoring method of CDT, age of participants and setting significantly ( p < 0.05) affect the sensitivity and specificity of the CDT. Conclusion: Although, the CDT is generally considered to be a simple and easy to administer screening tool for cognitive impairment in older hospitalised adults, when a more formal cognitive test is used its sensitivity and specificity to detect delirium is low.